Your first step. You added 4/3 to both sides. You needed to subtract.
4/3-4/3 -1/5t = 3/4-4/3
-1/5t = -7/12
-5* -1/5t = -5* -7/12
t = 35/12
2006-10-28 18:06:22
·
answer #1
·
answered by Anonymous
·
3⤊
0⤋
Hi:
Has far as I can tell you didn't do signs right and you didn't Simply your improper faction and prove your answer right
So:
4/3 - 1/5t = 3/4
- 4/3+ 4/3 - 1/5t = 3/4 - 4/3
-1/5t = 3/4 - 4/3
-1/5t= 9/12-16/12
-1/5t = -7/12
-1/5t = -7 / 12
-5/1 *(-1/5)t = -5*(-7/12)
t= 35/12
t= 2 11/12
Proof:
So
4/3 - 1/5t = 3/4
4/3- 1/5*(35/12) = 3/4
4/3- 35/60 = 3/4
80/60- 35/60 = 3/4
45/60 = 3/4
3/4= 3/4
So : 35/12 or 2 11/12 is the Correct answer
P.S: Watch your signs they will mess you up every time
2006-10-28 18:51:54
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
the problem is in first part
you have to eliminate the constant in the side of the equation where the variable is
so you have to add both side of the eq to its additive inverse
and the additive inverse of 4/3 is -4/3
4/3+4/3 - 1/5t =3/4 +4/3
will be 4/3 - 4/3 - 1/5t =3/4 -4/3
1/5t = 3/4 - 4/3
1/5t= 9/12 - 16/12
1/5t= -7/12
5/1x 1/5t =-7/12 x 5/1
t= 35/ 12
checking:
4/3 - 1/5t = 3/4
but t= 35/ 12
4/3 - 1/5(35/ 12) = 3/4
4/3 - 7/12 = 3/4
16/12 - 7/12 = 3/4
9/12 = 3/4
3/4 = 3/4
2006-10-28 18:18:23
·
answer #3
·
answered by lazareh 2
·
0⤊
0⤋
The very first line is wrong. If you want to eliminate 4/3 from the left side, which you have to, you should subtract 4/3 from both sides, not add it.
4/3 - 1/5t = 3/4
4/3 -4/3 -1/5t = 3/4 - 4/3
-1/5t = (9 - 16)/12 = - 7/12
-1/5t = -7/12
1/5t = 7/12
Now I have a question: is that 1/(5t) or (1/5)t?
if it is 1/(5t) then you get:
35t = 12 ------> t = 12/35
if it is (1/5)t then you get:
12t = 35 -------> t = 35/12
2006-10-28 18:16:09
·
answer #4
·
answered by smarties 6
·
0⤊
0⤋
its 4/3-4/3-1/5t=3/4-4/3
-1/5t=3/4-4/3
1/5t=4/3-3/4
1/5t=16-9/12
t=7/12*5
t=35/12
when u substitute t in the equation. U WILL GET THE ANSWER 3/4
2006-10-28 18:15:11
·
answer #5
·
answered by kalyan r 3
·
0⤊
0⤋
You left out the - sign from the 2nd step on.
JTRaceFan is right, too...
4/3 - 4/3 - 1/5t = 3/4 - 4/3
-1/5t = 3/4 - 4/3
-1/5t = 9/12 - 16/12
5/1x -1/5t = -7/12 x 5/1
-t = -35/12
t = 35/12
2006-10-28 18:06:54
·
answer #6
·
answered by Helmut 7
·
2⤊
2⤋
4/3 - 1/5t = 3/4
4/3 - 4/3 - 1/5t = 3/4 - 4/3
-1/5t = -7/12
t = 35/12
You're error is #1 adding instead of subtracting 4/3
#2 you didn't leave the - sign in front of 1/5 in your step 2.
2006-10-28 18:09:22
·
answer #7
·
answered by LaxPlayer35 1
·
2⤊
0⤋
first line : add 4/3 to both sides - looks alright
second line : line is erred..
you should have done:
first line: add (1/5t - 3/4) to both sides
u should get:
4/3 - 3/4 = 1/5t
16/12 - 9/12 = 1/5t
7/12 = 1/5 t
therefore multiplying both sides by 5
35/12 = t
2006-10-28 18:16:57
·
answer #8
·
answered by tutoronline 1
·
0⤊
0⤋
I will suggest to get the demonate out by
60(4/3 - 1/5t) = (3/4)60 now u have
80 - 12t = 45
see it's easier to work with because 60 is the comman demonate for all.
subtract 80 to both sides
80 - 12t = 45
-80 -80
-12t = -35
divide by -12
-12t/-12 = -35/-12
t = 2.91 repeating
round to 3 or 2.9
2006-10-28 18:15:18
·
answer #9
·
answered by Best Helper 4
·
0⤊
0⤋
4/3-1/5t=3/4
4/3-4/3-1/5t=3/4-4/3
-1/5t=-7/12
(-5)(-1/5t)=(-5)(-7/12)
t=35/12 or 2.91666~
2006-10-28 18:09:10
·
answer #10
·
answered by adamm128 1
·
1⤊
0⤋